Carbon Emissions, Economic Growth, Forest, Agricultural Land and Air Pollution in Indonesia - Azwardi, Azwardi; Sukanto, Sukanto; Igamo, Alghifari Mahdi; Kurniawan, Arika (International Journal of Energy Economics and Policy, 2021)
This study specifically analyzes the effect of motor vehicle emissions, economic growth of forest area, and agricultural area on air pollution in 33 Indonesian Provinces during the year 2010-2017 using the panel data regression approach. The results showed that (1) Carbon emissions and agricultural area in all regions in Indonesia had a negative and significant effect on the air quality index (2) Based on the regions of Sumatra Island, Java Island, and Kalimantan Island, GDP had a positive and insignificant effect on air pollution (3) Forest area in all regions in Indonesia, as a whole, has a positive and significant effect on the air quality index. Keywords: Air Pollution, Carbon Emissions, Economic Growth, Forests, Agriculture JEL Classifications: Q50, Q53 DOI: https://doi.org/10.32479/ijeep.11119